Therapeutic difficulties in a patient with Ehlers-Danlos syndrome and numerous symptomatic premature ventricular contractions—case report and literature review - Sławiński, Grzegorz; Wabich, Elżbieta; Hawryszko, Maja; Daniłowicz-Szymanowicz, Ludmiła; Chevalier, Philippe (Frontiers in Cardiovascular Medicine, 2023)
A 28-year-old female patient diagnosed with Ehlers-Danlos syndrome type III (hypermobile EDS, hEDS) was admitted to the cardiology clinic due to a 3-year history of symptomatic ventricular arrhythmia in the form of multiple premature ventricular contractions (PVCs).Attempts at antiarrhythmic treatment with beta-blockers, propafenone, and verapamil were unsuccessful. Due to the diagnosis of hEDS and the high risk of vascular complications related to the ablation procedure, invasive treatment was abandoned, and it was decided to implement flecainide. After the flecainide treatment initiation, a spectacular improvement in the number of ventricular arrhythmias was observed, along with the disappearance of the complaints previously reported by the patient. To the best of our knowledge, this is the first described case of spectacular flecainide antiarrhythmic effect in a patient with numerous PVCs also diagnosed with EDS. Flecainide treatment in the EDS group could be a successful alternative to ablation, which can lead to serious vascular and even life-threatening complications, especially after the failure of propafenone and beta-blockers treatment.